Curse and Blessing: A Postcolonial Study of Ngugi wa Thiong’o’s The River Between - Arif, Kawan Othman; Esamalddin, Hemn Salahalddin (Sulaimani Journal for Humanities, 2019)
The title of this paper is “Curse and Blessing: A Postcolonial Study of Ngugi wa Thiong’o’s The River Between”. Undeniably, colonialism is a political phase in history, known in the world as a dark stage particularly in the colonized countries. Nonetheless, colonialism can also have some bright aspects in addition to the calamities that it brought the colonized people. This paper studies how both dark and bright sides of colonialism are reflected in The River Between. The novel is written from the perspective of one of the colonized novelists which demonstrates and presents the two sides of colonialism. On the one hand, we see curses which have been inflicted by colonialism on the African people, which can be seen in the lives of characters such as ambivalence attitudes and feelings and identity crisis. On the other, there are blessings of colonialism such as education, public services and modern methods of administration that provide a more civilized frame to the colonized people.